2020
DOI: 10.3390/nano10010149
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal Nd-Doped LuVO4 Nanoprobes Functionalized with Polyacrilic Acid for X-Ray Computed Tomography and NIR Luminescent Imaging

Abstract: Uniform Nd3+-doped LuVO4 nanophosphors have been synthesized for the first time in literature by using a poliol-based method at 120 °C from Nd3+ and vanadate precursors. After optimizing the Nd doping level, these phosphors present intense luminescence in the near-infrared biological windows. The X-ray attenuation capacity of the optimum nanophosphor has been found to be higher than that of a commercial X-ray computed tomography contrast agent. After surface coating with polyacrylic acid, such nanoparticles pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
2
10
0
1
Order By: Relevance
“…PAA is a weak polyelectrolyte and has been used in several biomedical applications such as immunological studies, drug delivery, and enzyme immobilization. Many studies have revealed that PAA as a polymer is used in combination with other materials in various biomaterials (26,27,17).…”
Section: Discussion Discussionmentioning
confidence: 99%
“…PAA is a weak polyelectrolyte and has been used in several biomedical applications such as immunological studies, drug delivery, and enzyme immobilization. Many studies have revealed that PAA as a polymer is used in combination with other materials in various biomaterials (26,27,17).…”
Section: Discussion Discussionmentioning
confidence: 99%
“…Uniform Nd 3+ -doped LuVO 4 nanophosphors were produced and surface-coated with PAA; these nanoparticles are in a colloidal range in physiological pH range and have excellent stability to survive in the cell. Because of these features, these may be used as a bimodal probe for X-ray computed tomography and NIR luminous bioimaging [ 197 ] CdSe/Cu quantum dot conjugates with biocompatible polyacrylic acid functionalization were produced for bio labeling, bioimaging, and biomolecule detection applications [ 198 ].…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…CT, which can form 3D visual reconstruction of interested tissues given by the different X-rays attenuation degrees of different tissues, is a powerful noninvasive imaging technology with advantages of high spatial resolution, accurate anatomical information, and relatively affordable price ( Murakami and Nakahara, 2014 ). To further increase the visibility of internal body structure, CAs used in CT are required to provide different X-rays attenuation degrees from the surrounding organs ( Nunez et al, 2020 ). X-rays are thereby more or less absorbed by them than by body constituents, particularly by water.…”
Section: Bimodal Imaging Of Tumor Based On Near-infrared-i Fluorescencementioning
confidence: 99%